Discrepancy between clinical guidelines and real-world management of heart failure with reduced ejection fraction at University Medical Center Ho Chi Minh City, Vietnam - Hoang Vu Vu; The Dung Bui; Hai An Do; Dang Duy Quang Pham; Quang Binh Truong (BMC Cardiovascular Disorders)
Abstract Background Although guideline-directed medical therapy (GDMT) improves outcomes in patients with heart failure with reduced ejection fraction (HFrEF), multiple real-world studies - such as CHAMP-HF (USA) and ASIAN-HF (Asia-Pacific) - have reported that a large proportion of patients fail to reach target doses. This global gap between recommendations and practice highlights the need to better understand country-specific barriers, particularly in low- and middle-income settings such as Vietnam. Methods This cross-sectional study included adult outpatients diagnosed with HFrEF who had received at least three months of continuous therapy at the Heart Failure Clinic, University Medical Center Ho Chi Minh City, between February and August 2023, and aimed to (1) determine the prevalence of use, (2) evaluate typical dosages, and (3) examine the sequence of initiation of foundational therapies in this population. Findings Among 181 patients, 98.9% were prescribed at least one foundational drug class, and 74.6% received all four classes. Patients who did not receive all four therapies were typically older females with higher systolic blood pressure and reduced renal function. SGLT2 inhibitors and MRAs had the highest rates of target dose achievement, whereas ARNI and beta-blockers were more frequently underdosed. Dose escalation was commonly limited by hypotension, advanced age, renal impairment, and low body weight. Notably, 82% of patients were initiated on three or four drug classes concurrently at the start of treatment, most commonly including RAS inhibitors, MRAs, and beta-blockers, with a preference for ARNI over ACE inhibitors or ARBs. Interpretation Foundational therapies were widely prescribed and frequently initiated concurrently in the management of HFrEF at a tertiary care hospital in Vietnam. However, achieving target doses remains a challenge, highlighting the gap between clinical guidelines and real-world practice due to factors such as low blood pressure, advanced age, and renal dysfunction.